Bisphenol B stimulates Leydig cell proliferation but inhibits maturation in late pubertal rats. (July 2021) - Li, Yang; Yan, Haoni; Yu, Yige; Zou, Cheng; Tian, Lili; Xin, Xiu; Zhang, Song; Li, Zengqiang; Ma, Feifei; Ge, Ren-Shan
Abstract: Bisphenol B (BPB) has been used as a substitute for bisphenol A (BPA) in plastic materials. Whether BPB disrupts the male reproductive system remains unknown. Here, we report the effect of BPB on Leydig cell maturation in late puberty. Male Sprague-Dawley (35 days old) rats were gavaged with BPB at 0, 10, 100, and 200 mg/kg/day for 21 days. BPB significantly reduced body and epididymis weight at 200 mg/kg. BPB markedly decreased serum testosterone levels at 100 and 200 mg/kg and serum luteinizing hormone and follicle-stimulating hormone levels at 200 mg/kg. BPB significantly increased Leydig cell number at 100 and 200 mg/kg, while down-regulating the expression of Leydig cell genes ( Cyp11a1 and Hsd3b1 ) at ≥100 mg/kg and up-regulating the expression of Sertoli cell genes ( Pdgfra, Fshr, Sox9 ) and cell cycle regulators ( Pcna, Ccnb1, Cdk2, and Cdk4 ) at 10–200 mg/kg. BPB markedly increased the phosphorylation of AKT1, AKT2, and ERK1/2 at 200 mg/kg. BPB increased the proliferation of rat immature Leydig cells via promoting the S/M2 phase shift at 100 and 1000 nM after 24-h culture in vitro . In conclusion, BPB disrupts Leydig cell maturation in late puberty by increasing Leydig cell number while inhibiting its maturation. Graphical abstract: Graphic Abstract. Illustration of action of BPB on maturation of Leydig cell (LC) in late puberty . BPB might increase the number of LC precursors by activating the phosphorylation of AKT1, AKT2 and ERK1/2 and up-regulating the expression of cell cycle-related proteins (CDK1, CDK2, CDK4 and cyclin B1). BPB also inhibited the expression of Cyp11a1, Hsd3b1, Cyp17a1 and NR5a1 in individual LC. A combination of these mechanisms leads to a decrease in testosterone after BPB treatment. Image 1 Highlights: Bisphenol B reduces serum testosterone levels in late puberty. Bisphenol B increases Leydig cell number after exposure in late puberty. Bisphenol B down-regulates Leydig cell steroidogenesis-related gene expression. Bisphenol B induces the expression of cell cycle regulatory genes in the testis. Bisphenol B promotes the transition of Leydig cells to G2/M phases in vitro .